Design of a Textile Antenna Using Metasurface Technology for Wireless Body Area Networks - Sirait, Nurafifah; Fathurahman, Firhan; Alaydrus, Mudrik; Umaisaroh, Umaisaroh (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2024)
Recently, continuous development and distinctive growth have been observed in implementing wearable sensors and flexible devices in real life. This paper shows a wearable textile antenna design based on a metasurface. It operates in the 3.5 GHz. A proposed model provides light on the metasurface's operation. The prototype of the textile antenna using taslan material was observed and exhibited a relative permittivity of 1.41. Based on these values, we designed a square antenna with an amount of parasitic square around modeled as a planar array. We observed the measured reflection coefficient of the three conditions and saw similar results of the reflection coefficient, which is around -25 dB at 3.5 GHz frequency, and the radiation diagram of the antennas reproduced the simulated one.